[18F]DCFPyL PET-MRI/CT for unveiling a molecularly defined oligorecurrent prostate cancer state amenable for curative-intent ablative therapy: study protocol for a phase II trial. Issue 4 (22nd April 2020) - Glicksman, Rachel M; Metser, Ur; Valliant, John; Chung, Peter W; Fleshner, Neil E; Bristow, Robert G; Green, David; Finelli, Antonio; Hamilton, Robert; Stanescu, Teodor; Hussey, Douglas; Catton, Charles; et al.
Abstract : Introduction: The oligometastatic (OM) disease hypothesis of an intermediate metastatic state with limited distant disease deposits amenable for curative therapies remains debatable. Over a third of prostate cancer (PCa) patients treated with radical prostatectomy and postoperative radiotherapy experience disease recurrence; these patients are considered incurable by current standards. Often the recurrence cannot be localised by conventional imaging (CT and bone scan). Combined anatomical imaging with CT and/or MR with positron emission tomography (PET) using a novel second-generation prostate-specific membrane antigen (PSMA) probe, [ 18 F]DCFPyL, is a promising imaging modality to unveil disease deposits in these patients. A new and earlier molecularly defined oligorecurrent (OR) state may be amenable to focal-targeted ablative curative-intent therapies, such as stereotactic ablative radiotherapy (SABR) or surgery, thereby significantly delaying or completely avoiding the need for palliative therapies in men with recurrent PCa after maximal local treatments. Methods and analysis: This ongoing single-institution phase II study will enrol up to 75 patients total, to include up to 37 patients with response-evaluable disease, who have rising prostate-specific antigen (range 0.4–3.0 ng/mL) following maximal local therapies with no evidence of disease on conventional imaging. These patients will undergo [ 18 F]DCFPyL PET-MR/CT imaging to detect disease deposits, which will then be treated with SABR or surgery. The primary endpoints are performance of [ 18 F]DCFPyL PET-MR/CT, and treatment response rates following SABR or surgery. Demographics and disease characteristics will be summarised and analysed descriptively. Response rates will be described with waterfall plots and proportions. Ethics and dissemination: Ethics approval was obtained from the institutional Research Ethics Board. All patients will provide written informed consent. [ 18 F]DCFPyL has approval from Health Canada. The results of the study will be disseminated by the principal investigator. Patients will not be identifiable as individuals in any publication or presentation of this study. Trial registration numbers: NCT03160794